Adapting new norms: a mixed-method study exploring mental well-being challenges in dental technology education - Lin, Galvin Sim Siang; Tan, Wen Wu; Chua, Kah Hoay; Kim, Jong-Eun; Gan, Jin; Muhamad Halil, Mohd. Haikal (Public Library of Science, 2025)
Background The present study, grounded in the Stress-Adaptation-Growth theory, aims to explore the mental well-being among dental technology students during the post-pandemic period.